2020
DOI: 10.3892/etm.2020.8511
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary adenocarcinoma appearing as ground‑glass opacity nodules identified using non‑enhanced and contrast‑enhanced CT texture analysis: A retrospective analysis

Abstract: The present study aimed to investigate the ability of CT-based texture analysis to differentiate invasive adenocarcinoma (IA) from pre-invasive lesions (PIL) or minimally IA (MIA) appearing as ground-glass opacity (GGO) nodules, and to further compare the performance of non-enhanced CT (NECT) images with that of contrast-enhanced CT (CECT) images. A total of 77 patients with GGO nodules and surgically confirmed pulmonary adenocarcinoma were included in the present retrospective study. Each GGO nodule was manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In another study, reducing pixel size could improve the model performance in IAC prediction [45]. In this review, one included study [31] showed that radiomics model based on CECT images performed better than that based on NCECT images, which was not found in the other two included studies [33,41]. Segmentation influences the results of the radiomics analysis.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In another study, reducing pixel size could improve the model performance in IAC prediction [45]. In this review, one included study [31] showed that radiomics model based on CECT images performed better than that based on NCECT images, which was not found in the other two included studies [33,41]. Segmentation influences the results of the radiomics analysis.…”
Section: Discussionmentioning
confidence: 90%
“…The number of patients/nodules ranged between 34/34 and 794/886. Eight studies [15,[17][18][19][20][21][22][23] included only mixed ground-glass nodules (MGGNs), seven [24][25][26][27][28][29][30] only pure ground-glass nodules (PGGNs), and thirteen [14,16,[31][32][33][34][35][36][37][38][39][40][41] both of MGGNs and PGGNs.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations